2019
DOI: 10.1186/s12903-019-0864-8
|View full text |Cite
|
Sign up to set email alerts
|

Dental students’ awareness and attitudes toward HPV-related oral cancer: a cross sectional study at the University of Jordan

Abstract: Background The incidence of human papilloma virus (HPV)-related oral cancer has recently increased worldwide. The role of dentists is of prime importance in the early detection of oral cancer which would result in a favourable outcome for the patients. The aim of the current study was to assess the knowledge, awareness and attitudes of dental students, interns and postgraduate maxillofacial residents at the University of Jordan (UJ) to different aspects of oral cancer, particularly those related t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
37
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(60 citation statements)
references
References 51 publications
(44 reference statements)
5
37
1
3
Order By: Relevance
“…A cross-sectional study by Sallam et al found gaps in knowledge regarding HPV-related oral cancer among dental students, thus necessitating interventions such as curricular changes, training workshops, and awareness campaigns [14]. Nearly 88% of the students correctly identified HPV as a risk factor for oropharyngeal cancer development, compared to only 9.39% in the present study [14].…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…A cross-sectional study by Sallam et al found gaps in knowledge regarding HPV-related oral cancer among dental students, thus necessitating interventions such as curricular changes, training workshops, and awareness campaigns [14]. Nearly 88% of the students correctly identified HPV as a risk factor for oropharyngeal cancer development, compared to only 9.39% in the present study [14].…”
Section: Discussioncontrasting
confidence: 49%
“…A cross-sectional study by Sallam et al found gaps in knowledge regarding HPV-related oral cancer among dental students, thus necessitating interventions such as curricular changes, training workshops, and awareness campaigns [14]. Nearly 88% of the students correctly identified HPV as a risk factor for oropharyngeal cancer development, compared to only 9.39% in the present study [14]. Another study by Kepka et al revealed that up to 83.7% of oral health students believed that administering HPV knowledge and vaccination fell within the scope of practice of dental professionals, encouraging their participation in eradicating this virus [15].…”
Section: Discussionmentioning
confidence: 99%
“…Entretanto, barreiras sociais ainda precisam ser ultrapassadas para que esses profissionais consigam intervir de maneira eficaz em fatores determinantes para o processo de saúde-doença de seus pacientes [33][34][35] . Tais barreiras incluem, principalmente, a dificuldade da abordagem de assuntos relacionados a doenças sexualmente transmissíveis, como o HPV [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] .…”
Section: A Importância Da Atuação Do Cirurgião-dentistaunclassified
“…Ressalta-se, ainda, que o exame clínico e o adequado acompanhamento permitem que ocorra a detecção de diversas lesões, anomalias e alterações na cavidade bucal [22][23][24][25][26][27][28][29][30][31][32][33][34][35] . Ademais, a identificação precoce de lesões potencialmente malignas, como o carcinoma epidermoide bucal, permite que as chances de cura aumentem consideravelmente 33 .…”
Section: A Importância Da Atuação Do Cirurgião-dentistaunclassified
“…Globally, HPV knowledge and awareness has been reported to be low among the dental student, oral health student, and oral health professional populations; however, the construct validity of these instruments is questionable as many were study-speci c [14][15][16][17][18][19][20][21]. Likewise, studies that examine HPV knowledge and awareness in Latin American countries are limited, but point to suboptimal levels of knowledge and awareness of HPV in countries such as Brazil and Ecuador [22,23].…”
Section: Introductionmentioning
confidence: 99%